FROM SOURCES TO INTERPRETATION: WESTERN HISTORIOGRAPHY ON THE 1873 RUSSIAN CONQUEST OF THE KHANATE OF KHIVA - Nо‘mоnоv Kаmrоnbеk Kozimjon o’g’li (Web of Journals Publishing, 2025)
This article examines the 1873 conquest of the Khanate of Khiva by the Russian Empire and how this event was interpreted by Western historians of the 19th and early 20th centuries. It analyzes and compares the views of key foreign observers such as Henry Lansdell, Warren Walsh, Francis Skrine, and Januarius Aloysius MacGahan. Special attention is paid to the geopolitical causes, military operations, and the diplomatic maneuvers surrounding the conquest, as well as its broader historical implications. MacGahan’s eyewitness accounts, as documented in his works, serve as particularly valuable sources for reconstructing the events. The article adopts historical-comparative, source-critical, and contextual analytical methods.